Utilização do fíler de britagem em concretos autoadensáveis visando à redução do consumo de cimento - Preis, Deivid Willian (2023)
Self-compacting concrete (SCC) is characterized by simultaneously obtaining fluidity, cohesion and passing ability. To obtain these properties, the dosage requires a greater volume of fines in the paste composition. In this scenario, the use of additions in SCC seeks to improve the self-compacting characteristics, reduce concrete costs and use waste that reduces environmental impacts caused by CO2 emissions in the manufacture of cement. Additions commonly used in CAA are fine materials that aim to guarantee the properties of CAA. Therefore, it becomes interesting to use alternative fillers of mineralogical origins, such as that of basaltic origin (FB), which is generated in crushing fields, resulting in storage, health and environmental pollution problems as it is not used on a gradual scale. In view of the above, the present work aims to verify the segregation control of CAA made with FB in the proportions of 5%, 10%, 15%, 20%, 25% and 30%, in addition to encouraging the reduction of consumption of cement. The fresh state results showed performance of fluidity, cohesion and passing ability in substitutions of 5 to 25%. In the hardened state, as the content of cement replacement by FB increased, a reduction in compressive and tensile strength was observed, which was expected due to the decrease in cement consumption. In the absorption test, a significant increase in porosity associated with the lamellar shape of the FB grain was observed. Finally, the use of FB to replace up to 25% of cement showed satisfactory results in the fresh state and presented resistance greater than 30 MPa at 90 days, demonstrating innovative potential for improving the sustainability of civil construction.